Schedulability analysis of server-based error-recovery mechanisms for time-triggered systems - Marques, Luis; Vasconcelos, Veronica; Pedreiras, Paulo; Almeida, Luis (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2013)
Distributed Embedded Systems are subject to transient communication faults that need being detected and mitigated in safety-critical scopes. This paper addresses error recovery in time-triggered systems based on the Controller Area Network (CAN). It extends a recent work that proposed using online traffic scheduling, combined with servers, to implement dynamic message retransmissions. In particular, we provide a schedulability analysis that considers the interference of the error-recovery server in the time-triggered traffic, as well as a methodology to compute the worst-case response time of messages affected by errors. We also present a comparison with related error-recovery methods that confirms the superiority of the proposed method.